Implementasi Pembelajaran Daring Berbasis Whatsapp Group dan Imtera - Binti Hidayati Jazilatur Rohmah; Marita Lailia Rahman (Lembag, 2025)
At the beginning of 2020, Indonesia faced a difficult time due to the Covid-19 pandemic, which significantly affected the education system. Traditional face-to-face teaching was replaced with an online learning system. This research aims to describe the planning, implementation, and evaluation of online learning using WhatsApp Group and the IMTERA application. The study employed a qualitative research approach, with data collected from both primary and secondary sources through observation, interviews, and documentation. The data analysis technique used is descriptive, involving three steps: data reduction, data display, and conclusion drawing. The findings show: (1) Online learning planning based on WhatsApp Group and IMTERA at MI PSM Dadapan Nganjuk was well prepared, including setting learning objectives and choosing appropriate media. (2) In implementation, teachers delivered materials and assignments via WhatsApp groups and the IMTERA app, allowing for flexible and asynchronous communication. (3) Evaluation was conducted both qualitatively and quantitatively. Qualitative assessment involved descriptive feedback, while quantitative assessment provided scores for student tasks. Teachers also considered students' activeness and responsibility in completing assignments as part of the evaluation. This shows that the school adapted well to online learning challenges during the pandemic.